The efficiency of free PSA index in the diagnosis of prostate cancer - Ortiz, José (2015)
Determining the efficiency of testing free PSA index in the diagnosis of prostate cancer. Design: Retrospective study. Location: Edgardo Rebagliati Martins National Hospital, EsSalud, Lima, Peru. Participants: Patients undergoing prostate biopsy. Interventions: Collection of data from 371 patients undergoing prostate biopsy -104 cases of prostate cancer and 267 cases of benign hyperplasia próstata-, by review of hospital medical records and review of pathological studies. Main outcome measures: Sensitivity, specificity, positive predictive value, negative predictive value, ROC curve (receiver operating characteristic) and area under the ROC curve (AUC) curve. Results: The rate of free PSA with the cutoff used in clinical practice of 0.20 showed a sensitivity of 0.85, specificity of 0.51, positive predictive value of 0.41, negative predictive value 0.90. The cutoff with a sensitivity of 0.95 was obtained 0.28. The area under the ROC curve was 0.78. Conclusions: The test demonstrated free PSA index improving the specificity of total PSA to avoid unnecessary biopsies. Be advisable to raise the cutoff of 0.20 used to increase the sensitivity of the test to 95%, to avoid the loss of detected cases of prostate cancer.